The Influence of the Quality of Service and the Implementation of the Policy of Return Administration at Inpatient Room Towards Satisfaction of Third Class of BPJS Patient in Muhamadiyah University Hospitals at Malang - Maria Maria; Byba Melda Suhita; Yuly Peristiowati (Journal for Quality in Public Health, 2020)
The purpose of this research was to analyze the influence of the quality of service and the implementation of the policy of return administration at inpatient room towards satisfaction of third class of BPJS patient at RS UMM. Design of this research are analysis crossectional. Variable of the research are. the influence of quality of service and the implementation of the policy as the independent variable and patient satisfaction as the dependent variable BPJS. Population research namely inpatients who have been allowed to return home on October 15 – November 15, 2018 by the physician in question at the time when the last doctor's visit. Samples taken by random sampling technique as much as 92 respondents. The data collected by the instruments and questionnaires processed in coding, editing, tabulating and scoring as well as tested with linear regression test. Linear regression results indicate that partially and the simultaneous values of p values there are shows so that 0.05 < influence the quality of services and the implementation of the policy to the satisfaction of the patient. he value of the coefficient of determination shows the value that shows contributions from 0.434 independent variable (the quality of service and policy implementation) amounted to 43.4%, while the remaining 56.6% in influence by other factors not present in the model This research. This happens because the factor that affect patient satisfaction is not only seen from the implementation of policies and the quality of services, but there is another factor that could affect such facilities or the attitude of the officers. Quality of service and implementation of the return of the patient affect the satisfaction of the patient. This happens because with the delay time return for the patient, or the patient's waiting too long is also the process of their return would cause a negative perception of the patient so that the patient feels accepted slow service